Law and Representation: Gender, Power, and Religious Narratives in Indonesian Film - Kusumaningtyas, Shela (Faculty of Law, Universitas Pekalongan, 2025)
This article critically examines the intersection of gender, power, and religious ideology in the Indonesian film Tuhan, Izinkan Aku Berdosa, using Roland Barthes’ semiotic framework within a communication studies perspective. By analyzing the denotative, connotative, and mythical meanings of key visual elements—such as the hijab, spatial dynamics, lighting, and body language—the study reveals how symbolic narratives in the film reproduce patriarchal discourse and religious authority that regulate women’s bodies and moral identities. Film, as a form of mediated communication, functions not merely as entertainment but as a powerful ideological text that shapes public perception, reinforces cultural myths, and contributes to the construction of social norms. Building upon this, the article expands the analysis by connecting the film’s symbolic representations to Indonesia’s legal and policy frameworks, including Islamic family law, local moral regulations (Perda Syariah), and recent legislation on sexual violence. Through this interdisciplinary approach, the study engages feminist legal theory and reformist Islamic scholarship to show how cinematic representations both reflect and challenge institutionalized gender inequality. The findings demonstrate that visual communication in film can serve as a discursive arena for negotiating religious authority, exposing moral hypocrisy, and contesting legal injustices. Ultimately, this study underscores the critical role of film as a medium of cultural resistance and legal reflection in contemporary Indonesian society.